On ΛpBV-Solutions of Some Nonlinear Integral Equations on the Plane - Jurancy Ereú; Liliana Pérez; Luz Rodríguez (International Journal of Differential Equations)
In this paper, we define the space of functions Λp-bounded variation on the plane and endow it with a norm under which it is a Banach space. In addition, we study some nonlinear integral equations and providing conditions for the functions and kernel involved in such equations under which we guarantee the existence and uniqueness in the space of functions of bounded variation in the sense of Shiba on the plane, ΛpBVIab,ℝ.